Caracterización de la generación de residuos sólidos no municipales en pabellón A-10 - facultad de agronomía - Zagaceta Soto, Willo Juan Diego (2019)
The present thesis had as object to characterize the non-municipal solid waste generated in the hall A-10 of the Faculty of Agronomy of the National University of the Peruvian Amazon, in the university city of Zungarococha for a period of three weeks, with a daily population of 300 students. The information has been collect from the primary source that comprised to the students, who use this hall and their consumption habits during the development of their academic activities. As part of the evaluation different activities has been develop, being these awareness talks about the segregation of solid waste, organization of work teams for the process of segregation and development of composting activities. At the end of the evaluation has been find that the per capita generation (PCG) in the hall A-10 was of 0.0091 kg/hab/day, and its projection of generation based on the value of the PCG obtained was of 0.0051 t/day, 0.152 t/month and 1,821 t/year. The non-municipal solid waste characterized has been distribute in non-hazardous was with 68.60% of the evaluated, of which 14.19% is organic and 54.41% is inorganic. Likewise, it has been find that of the total of non-municipal solid waste 0.25 t are compostable waste.